PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN IMAGE TERHADAP KEPUASAN NASABAH YANG MENABUNG PADA PT. BANK SULSELBAR - Muhammad Fuad Randy (Jurnal Bisnis dan Kewirausahaan, 2016)
The purpose of this study was to determine and analyze the quality of service, trust and image effect on customer satisfaction save on PT. Sulselbar Bank, as well as to identify and analyze between service quality, trust and image, where the dominant influence on customer satisfaction save on PT. Bank Sulselbar. This study used quantitative descriptive method. Population and samples are 118 respondents (full sampling). Data analysis technique in this research is multiple linear regression analysis. The study found that simultaneous service quality, trust and image effect on customer satisfaction save on PT. Bank Sulselbar Makassar based acquisition Fhitung 72 254 with a probability level of 0.000 (significant). While Ftable by 4.9646 thus the disappearance of F larger than F table (72 258> 4.9646 and also the probability of much less than 0.05. Based on t test to test the significance or the significance of regression coefficients partial showing that partial service quality, trust and image significantly affect satisfaction customer at PT. Bank Sulselbar Makassar. It was found that the quality of the service was the dominant influence on customer satisfaction save at PT. Bank Sulselbar Makassar based on the regression coefficient (B) of 0584 The advice given in terms of improving the quality of services, PT. Bank Sulselbar Makassar need to make improvements to provide services quickly and accurately to meet customer satisfaction.